Coronary artery thrombosis in patients with unstable angina. Issue 4 (April 1981) - Holmes, D R; Hartzler, G O; Smith, H C; Fuster, V
Abstract : This report describes the clinical course, coronary artery anatomy, and ventricular function of 16 patients in whom coronary artery thrombosis was detected at the time of cardiac catheterisation. All patients had an unstable clinical course in which accelerated angina occurred a mean of four weeks (range four days to 12 weeks) before catheterisation, and four patients had recent subendocardial myocardial infarction. In all patients severe coronary artery disease was documented at catheterisation. Fifteen patients had segmental wall motion abnormalities involving the left ventricular wall that was supplied by the coronary artery in which there was thrombus. Three patterns of coronary artery thrombus were noted: (1) Thrombus proximal to high-grade coronary artery stenosis; (2) thrombus distal to high-grade coronary artery stenosis; and (3) thrombus in segments of the arterial tree in which there was no high-grade coronary artery stenosis. Though the precise cause of the coronary artery thrombosis in our patients is unknown, it may have been a result of stasis, a ruptured atherosclerotic plaque, or coronary spasm. The common clinical course with unstable angina of acute onset suggests the possibility that the thrombus may have been responsible for the abrupt change in clinical condition or may have been a contributing factor in the patients' course.